Examining the Performance of Palm-Oil-Based Surfactant in Increasing Oil Recovery Through Spontaneous Imbibition Test: A Case Study in Light Crude Oil - Eryko Despriady (Proklamasi 45 University, 2022)
Along with the increasing demand for oil and decreasing production every year, we are faced with the challenge of being able to maximize the potential of our oil resources. The decline in production in Indonesia is largely due to the fact that Indonesia's oil fields which are still operating today are mature fields whose production is already very low. Enhanced Oil Recovery (EOR) is one method that has been proven capable of producing residual oil in a field. One type is Chemical Enhanced Oil Recovery (CEOR) which injects chemicals to increase oil mobility. Surfactants are chemicals that have been widely applied for chemical injection. Its ability to reduce interfacial tension (IFT) and alter rock wettability is the main mechanism of surfactants. In this test, the surfactant used is a palm-based surfactant and will be applied to light oil. Tests such as compatibility test, IFT test, contact angle test, and spontaneous imbibition test were carried out to get a conclusion about the performance of a surfactant. In the compatibility test, the samples in this study all formed a hazy solution at all test concentrations. IFT measurements carried out showed that surfactants were able to achieve an IFT value of 10-3 (ultralow) at a concentration of 0.5%. In addition, based on the contact angle test, samples of surfactant X 0.5% and 0.3% were able to form a smaller contact angle than brine. To measure the performance of surfactant in increasing oil recovery, a spontaneous imbibition test was carried out and the results were that both samples of surfactant X 0.3% and X 0.5% were able to produce recovery factors of 53.5% and 54.2%, which were greater than the recovery factor of brine, which was 43.7%.